Effect of China's zero-tariff treatment under forum on China-Africa Cooperation (FOCAC) on export diversification in beneficiary countries in Africa - Zhina Sun; Michael Mitchell Omoruyi Ehizuelen (Journal of African Trade, 2021)
In this study, we quantitatively assessed the effect of China's zero-tariff treatment on export diversification in beneficiary countries in Africa. We assessed its overall effect and its effect on particular industries and regions. The results showed that, overall, zero-tariff treatment significantly promoted export diversification. At the level of industry, zero-tariff treatment had a significant role in promoting the diversification of exports from the manufacturing industry, but did not significantly affect agriculture or mining. At the regional level, zero-tariff treatment significantly promoted export diversification among group members belonging to four major regional economic communities in Africa, albeit to varying degrees. Furthermore, three recommendations are proposed for improving the effect of zero-tariff treatment: expanding the use of benefits across regional groupings, reducing non-tariff barriers, and supporting African countries to enhance exports and production capacity.
Keywords: 330; China; zero-tariff treatment; export diversification; Africa; Forum on China-Africa Cooperation